The Existence of a Complete Systematic Land Registration System (PTSL) - Ade Riusma Ariyana; Devina Arifani (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
This research aim to understand the complete land registration which has a function in giving legal force to land owners in the life of today's society. Such a situation is clear that it is very supportive of people's lives related to the use of land, including in terms of economic activities. The problem of disruption that is present in the current era of economic globalization requires innovation in various fields of people's lives that are able to make people's lives easier, including in terms of Complete Systematic Land Registration or PTSL. Law as a tool of social engineering, the substance of the law, besides being regulatory, must also be coercive. The coercive nature of the law embodied in a legal product (statutory regulations) will be effective if there are sanctions for non-compliance or violation of the provisions stipulated by law. The substance of Article 23 paragraph (1) of the BAL, emphasizes that property rights, as well as any transfer of building use rights and the imposition of other rights must be registered according to the provisions referred to in Article 19. This provision explicitly obliges property rights holders to register every transfer of rights ownership of land, whether it is the transfer of ownership rights due to buying and selling, grants and so on.However, the provisions of Article 23 paragraph (1) of the UUPA which are imperative in nature do not have coercive power, because there are no strict sanctions for those who do not register any transfer of rights as referred to in the article. The implementation of PTSL as an alternative in answering the problem of the effectiveness of land registration has not been able to materialize. The method in this writing is quantitative. Based on the existing studies, it can be understood that PTSL, which is a new alternative, has not been able to be implemented effectively.